Increased orienting to unexpected action outcomes in schizophrenia - Nunez Castellar, Elena; Houtman, Femke; Gevers, Wim; Morrens, Manuel; Vermeylen, Sara; Sabbe, Bernard; Notebaert, Wim (Frontiers in Human Neuroscience, 2012)
Although some recent research has indicated reduced performance monitoring in patients with schizophrenia, the literature on this topic shows some remarkable inconsistencies. While most studies suggest diminished error signals following error responses, some studies reported normal post-error slowing, while others reported reduced post-error slowing. Here we review these studies and highlight the most important discrepancies. Furthermore, we argue that overall error rates are a mostly neglected issue that can at least partly explain these discrepancies. It has been reported previously that post-error slowing depends on the error rates. Participants or patients that make more errors are likely to show decreased post-error slowing. Therefore, when a group of patients is compared to a group of controls, it is extremely important to match error rates. For this purpose, we developed a procedure where we matched individuals’ error rates. In a task where subjects had to press a response key corresponding to one of four colors we manipulated the difficulty on an individual basis by varying the discriminability between the colors. Schizophrenic patients and a group of controls were tested with this procedure showing that differences in accuracy disappear. Interestingly, we can see that in patients, the color values that were needed to reach similar levels of accuracy correlate with the PANSS scale, with higher PANSS requiring more color. Most important, we found that schizophrenic patients have increased rather than decreased post-error slowing when the intertrial interval is short. This result can be interpreted within the framework of the orienting account, as it has been demonstrated previously that schizophrenic patients show increased distractibility.